Converting readers to patients? From free to paid knowledge-sharing in online health communities. Issue 3 (May 2021) - Meng, Fanbo; Zhang, Xiaofei; Liu, Libo; Ren, Changchang
Highlights: OHCs enable physicians to share both general and specific health knowledge. General knowledge-sharing is positively associated with specific knowledge-sharing through online reputation. Patient involvement strengthens the effects of general knowledge-sharing on online reputation and specific knowledge-sharing. General knowledge-sharing can be an efficient approach for physicians to recruiting patients. Abstract: Although the sharing of knowledge in online health communities (OHCs) has been explored in recent years, little research has been done to explore the relationship between general and specific knowledge-sharing. Based on the literature on knowledge-sharing in OHCs, this study developed a research model to explore how physicians' general knowledge-sharing behaviors influence their specific knowledge-sharing activities via their online reputations and the contingent role of patient involvement in OHCs. The research model was tested using objective data from a leading OHC in China. The results show that general knowledge-sharing is positively associated with specific knowledge-sharing, and this effect is exerted through online reputation. Moreover, patient involvement strengthens the relationship between general and specific knowledge-sharing as well as the relationship between online reputation and specific knowledge-sharing. By uncovering the relationship between general and specific knowledge-sharing, the research findings extend the understanding of knowledge-sharing and patient recruiting in OHCs and provide significant practical implications for practitioners.